Evaluation of The Wirid Youth Program Using The CIPO Model - Wardiman, Jery; Latifannisa, Nuri; Rahmi, Yuri; Friyatmi; Susanti, Dessi (Ta'dib, 2024)
This study evaluates the Wirid Youth Program implemented at SMAN 2 Lengayang in Pesisir Selatan Regency, aimed at reducing juvenile delinquency and shaping student character. This study adopts a quantitative research paradigm. The evaluation employed the CIPO method (Context, Input, Process, Output) through surveys and interviews with randomly selected participants. The validity of questionnaire items was tested using the Pearson Product Moment formula. The data analysis technique with data collection, data reduction, data presentation, and verification and conclusion drawing. The findings reveal that all program components context, input, process, and output are rated highly. The program effectively addresses teenagers' needs and challenges, provides accessible locations and satisfactory facilities, and is smoothly coordinated. As a result, there is increased teenage participation, enhanced religious knowledge, and positive behavioral changes. The program has met its objectives and positively impacted the participants. This evaluation underscores the program’s success and offers insights for future improvements and program development.